Charter School Entry and School Choice : The Case of Washington, D.C. - Ferreyra, Maria Marta (World Bank, Washington, DC, 2015)
This paper develops and estimates an equilibrium model of charter school entry and school choice. In the model, households choose among public, private, and charter schools, and a regulator authorizes charter entry and mandates charter exit. The model is estimated for Washington, D.C. According to the estimates, charters generate net social gains by providing additional school options, and they benefit non-white, low-income, and middle-school students the most. Further, policies that raise the supply of prospective charter entrants in combination with high authorization standards enhance social welfare.